Discourse “Declaration of Love”: Problem of Automatic Identification (Works of A. P. Chekhov») - L. G. Babenko (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The problem of revealing the “Declaration of Love” discourse in works of art is considered. The author’s development on the automatic detection of the situation of declaration of love, tested on the material of the work of A. P. Chekhov, is presented. The search was carried out on the basis of the Russian National Corpus. In total, more than 200 texts have been identified containing textual representations of the situation of declaration of love. 40 out of 200 texts are identified by the authors of the article as the most fully representative of the desired situation. The set of textual passages describing it is viewed as a cognitive-discursive set of declarations of love. The development of the algorithm was carried out based on the identification of the cognitive schemes of the writer and the statistical analysis of the lexical composition of the situation of declaration of love. Among the frequency components of the cognitive model, which A. P. Chekhov follows in describing the process of declaring love, an open space filled with plants, birds, etc. was revealed. In the general cognitive-discursive set of declarations of love, the nuclear and satellite zones were identified and analyzed, the lexical components of which belong to certain functional-semantic classes and functional-semantic groups.